Unfree Lives - Moorthy Kloss, Magdalena (Brill, 2024)
This first detailed study of slavery in medieval Yemen examines the lives of women and men who were enslaved as children and then placed in various subaltern positions - from domestic servant to royal concubine, from quarryman to army commander.